On the two-point boundary value problems using variational-fixed point iterative scheme - Wadai, Mutah; Kilicman, Adem (Institute for Mathematical Research, Universiti Putra Malaysia, 2017)
We developed a new scheme which is obtained by linking finite element, fixed point iterations and variational iteration technique known as variational-fixed point iterative scheme for attacking higher order differential equations. The finite element method is use to obtain the first approximation of VIM, while its the first order approximations is taken as starting value of fixed point iteration method, these sequence give an added advantage over the existing methods. The method is practically applicable to the experiment presented and comparisons were made with exact solution and other methods to demonstrate its reliability, comfortability as well as efficiency of the method.